The course virtualization experience at the University of Costa Rica - Zamora-Serrano, Evelyn (2022)
The University of Costa Rica has faced the challenge in the last two years of using virtual mechanisms for the development of its courses. The objective of this article is to analyze the experience that the student population lived from the virtualization of courses and the use of technological means given the suspension of face-to-face classes that occurred due to the COVID-19 pandemic during cycles I and II of the year 2020. Likewise, it aims to assess the qualification offered by the student body to the teaching performance in the synchronous and asynchronous remote classes. The results reveal that the experience of virtualization of courses and the teaching performance in this modality was perceived positively by the student population.